Asymmetries in international environmental agreements - Pavlova, Yulia; de Zeeuw, Aart (Cambridge Journals, 2013)
This paper considers self-enforcing international environmental agreements when countries are asymmetric with respect to emission-related benefits and environmental damage. Considering these asymmetries simultaneously yields large stable coalitions, also without the option of transfers between signatories. However, these large stable coalitions are only possible if they include countries that have relatively high marginal benefits and a relatively low marginal environmental damage. This type of countries hardly contributes to the common good and the gains of cooperation from including this type of countries in the stable coalition are small. This confirms a persistent result in this literature that large stable coalitions usually go hand in hand with low gains of cooperation. Without the option of transfers it is always better to have a small stable coalition with countries that matter than a large stable coalition with countries that do not matter. Only with transfers might a large stable coalition be able to perform better.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; kansainväliset sopimukset; international agreements; environmental protection; ympäristöoikeus